Simultaneous biogas upgrading, CO2 sequestration, and biogas slurry decrement using biomass ash. (September 2021) - Feng, Liang; Liang, Feihong; Xu, Lang; Ji, Long; He, Qingyao; Yan, Shuiping
Graphical abstract: Highlights: A novel system for CO2 sequestration and biogas slurry decrement is put forward. A high CO2 sequestration capacity of 129.94 g-CO2 /kg is acquired. The CO2 -rich biomass ash and biogas slurry mixture is applied for plant growth. Abstract: A novel system for simultaneous biogas upgrading, CO2 sequestration, and biogas slurry decrement was established by adding biomass ash into biogas slurry to form a renewable CO2 mixture absorbent. After CO2 saturation, the CO2 -rich mixture absorbent could be applied for plant growth. When the mass ratio of liquid to solid was 4:1, CO2 absorption capacity of this mixture absorbent reached up to 97.33 g-CO2 /kg-biomass-ash, which was about 135% higher than that of the biomass ash-water mixture. The highest value of 129.94 g-CO2 /kg-biomass-ash was obtained at a liquid–solid ratio of 99:1. When the TS concentration of anaerobic digestion feedstock was higher than 16 wt% and the water content of CO2 -rich absorbent was about 50 wt%, more than 80% of biogas slurry can be adsorbed by the biomass ash. If the biomass ash with a CO2 absorption capacity of 100 g-CO2 /kg was adopted and its transportation distance was less than 45 km, the biogas upgrading cost could be lower than the global average level (about RMB¥ 0.7/Nm 3 -biogas) when using the novel system proposed in this study.